علم الاستشراف والتوقع (السيناريو) بين الفكر الإسلامي والفكر الغربي: The Science of Foresight and Prediction (Scenario) Between Islamic Thought and Western Thought - Hasan Saleh, AbdulMajid Obaid; Akbar, Kieren (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
الاستشراف أو فقه التوقع من أهم أدوات الفقهاء في استعداد النازلة قبل وقوعها. باستشراف المشاهد -وذلك بواسطة التبصرة والمقربات العقلية- يمكن أن يؤل إليها الفقيه المسلم فبل وقوعها في المستقبل. ولكن الإشكال، فرض السيناريو واستشرافه قبل وقوعه لم يهتم الفقهاء في ذلك نظراً بقلة الكتب أو المقالات أو البحوث المتعلقة بها. كذلك التعمق في هذا الموضوع بمطالعة الكتب التراث الإسلامية بإضافة إلى المراجع الغربية. استخدم الباحث المنهج الاستقرائي في التعامل مع والمعلومات والبيانات والتفاصيل فيما يتعلق بفقه التوقع والاستشراف من ناحية الفكر الإسلامي والغربي. ثم المنهج التحليلي وذلك بتحليل موضوع فقه التوقع بكافة جوانبها الشرعية وشرحها ويستنبط منها حتى يوضح الأمر والحكم عنه. والنتيجة، فقه التوقع أو أحيانًا بمصطلح فقه المآلات مهم في تكوين عقلية الفقيه المسلم، وذلك من خلال دراسة عميقة واستعداد النازلة قبل وقوعها. أما الغرب، رأى أهمية هذا الفن لأنه منهجية للتفكير العقلاني العميق الذي يستند لأدلة وشواهد محسوسة أو مقبولة عقلاً تسهم بقدر في التنبوء بمالات المستقبل، وتعددت المدارس المستقبلية التي أنشئت في الأروبا لدراسة هذا الفن. Foresight or the jurisprudence of anticipation is one of the most important tools of the Muslim jurists in preparing for the calamity before it occurs. By anticipating the scenes - by means of insight and mental approaches - the Muslim jurist can refer to them before they occur in the future. But the problem is, imposing the scenario and foreseeing it before it happens, the jurists did not care about this topic as it depicted to the few numbers of books, articles or research related to it. As well as delving into this subject by reading Islamic heritage books in addition to Western references. The researcher used the inductive approach in dealing with information, data and details regarding the jurisprudence of anticipation and foresight in terms of Islamic and Western thought. Then the analytical approach by analyzing the subject of the jurisprudence of expectation in all its legal aspects and explaining them and deducing from them in order to clarify the matter and the ruling on it. As a result, the jurisprudence of anticipation or sometimes in the term of jurisprudence of fate is important in forming the mentality of the Muslim jurist, through a deep study and preparation for the calamity before it occurs. As for the West, it saw the importance of this knowledge because it is a methodology of deep rational thinking that is based on evidence and evidence that is tangible or acceptable to the mind, which contributes as much to predicting the fortunes of the future, and there are many future schools that were established in Europe to study this knowledge.